Diagnosis of Xanthomonas axonopodis pv. citri, causal agent of citrus canker, in commercial fruits by isolation and PCR-based methods - Golmohammadi, Morteza; Cubero, Jaime; Penyalver, Jaime; Quesada, Jose M.; López, María M.; Llop, Pablo (Society for Applied Microbiology, 2022)
Aims: To show the results of the detection of an EU quarantine organism, Xanthomonas axonopodis pv. citri (Xac), in citrus fruits imported from countries where this bacterium is present, using an integrated approach that includes isolation, pathogenicity assays and molecular techniques. Methods and Results: Citrus fruits with canker-like symptoms, exported to Spain from South American countries were analysed by several methods. Bacterial isolation, three conventional polymerase chain reaction (PCR) protocols, and real-time PCR with SYBR Green or a TaqMan probe, were compared. Canker-like lesions were disrupted in PBS buffer, and the extract used for bacterial isolation and DNA extraction followed by PCR amplification. Canker lesions, identified by PCR, showed viable bacteria in eleven of fifteen fruit samples. In 16 out of 130 lesions analysed from these samples, Xac was isolated, and pathogenicity on grapefruit leaves confirmed. By real-time PCR, using SYBR green or a Taqman probe, Xac was detected in 58 and 80 lesions respectively. By conventional PCR the bacterium was detected in 39–52 lesions depending on the protocol employed. Conclusions: An integrated approach for reliable detection of Xac in lesions of fruit samples, employing several techniques and with real-time PCR using a TaqMan probe as the fastest and most sensitive screening method, has been established and validated and is proposed as a useful tool for the analysis of Xac on fresh fruits. Significance and Impact of the Study: This work faces up to the real threat of the importation of citrus fruits that can harbour quarantine bacteria and will be useful in diagnostic laboratories for the analysis of commercial fresh fruits from countries where citrus canker is present.